ANALISIS PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK XIOMI DI SURAKARTA - Wicaksono, Adik Wahyu (2017)
This research target is to analyze the product quality to decision purchasing handphone of brand Xiomi: TTo analyze the, price to decision purchasing handphone brand Xioami. To analyse the promotion to purchasing handphone brand Xiomi. Population in this research buyer handphone brand Xiomi Surakarta which buyer amount too big hence, researcher sum up the samX1 as much 100 responder which is there are in the population. Pursuant to has result analyses the test t known that product quality (XI) have the influence which significant to purchasing decision pick hack assess the t.sig (0, 000) smaller than 0, 05, hence individually product quality (XI) have an effect on positive to purchasing decision. Price (X7) have the influence which significant to purchasing decision (Y) and supported value t. s ig (0, OOQJ smaller than 0, 05, hence individually price ( X2) have an effect on positive to purchasing decision (Y). Promotion (X3) have the influence which significant to purchasing decision (1) and supported value t. sig (0, OOO) smaller than 0, 05, hence individually promotion (X3J have an effect on positive purchasing decision M. Result of analysis test the F obtained Tcount Ftable (3-7,497 > 3,15), hence Ho refused, Mean by together variable product quality MJ, price (X21 and promotion (X31 have an effect on the significant purchasing decision (Y). So that model used in this research can be told Pursuant to result analyses the coefficient determinist (A) obtained adjusted R square ) equal to 01, 525, meaning variation of change of explainable purchasing decision variable by variable product quality (XI), price (X2) and promotion (X3) equal to 52,5%. While the rest equal to 4 7, 1 % explained by other variable outside model Fit.